1993
DOI: 10.1038/hdy.1993.147
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of genetic variability in chrysanthemum (Dendranthema grandiflora Tzvelev) using random primers

Abstract: Genetic variation in chrysanthemum (Dendranthema grandifiora) was studied using a recently developed technique generating Random Amplified Polymorphic DNAs (RAPDs). It appeared that variation between cultivars was high and that the cultivars used could be distinguished from each other by using only two different primers. A family of cultivars, derived from one original cultivar by vegetative propagation, had identical fragment patterns. Because of the high level of polymorphism and clonal stability RAPD fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 37 publications
(34 reference statements)
1
49
1
1
Order By: Relevance
“…Alternatively, diagnostic marker bands of parents may have been lost from S. cambrensis due to rapid genomic change, which is believed to occur in new allopolyploids more commonly than previously assumed (Soltis & Soltis 1999, 2000. A third possibility is that band absence is due to the effect of ploidy upon competition processes in RAPD-PCR reactions (Wolff & Peters-Van Rijn 1993;Weising et al 1995). Because S. cambrensis contains a larger genome than S. squalidus, it is expected to possess more sites of 100% sequence similarity to a particular primer.…”
Section: Genomic Composition Of Hybrid Derivatives Of Senecio Squalidmentioning
confidence: 99%
“…Alternatively, diagnostic marker bands of parents may have been lost from S. cambrensis due to rapid genomic change, which is believed to occur in new allopolyploids more commonly than previously assumed (Soltis & Soltis 1999, 2000. A third possibility is that band absence is due to the effect of ploidy upon competition processes in RAPD-PCR reactions (Wolff & Peters-Van Rijn 1993;Weising et al 1995). Because S. cambrensis contains a larger genome than S. squalidus, it is expected to possess more sites of 100% sequence similarity to a particular primer.…”
Section: Genomic Composition Of Hybrid Derivatives Of Senecio Squalidmentioning
confidence: 99%
“…These techniques have been applied to wild species to answer specific questions, mainly regarding the crossing system (Hayward and Hamilton, 1997). Some studies based on microsatellites have been employed in the study of natural populations (Collevatti et al, 2001;Zucchi et al, 2003) but most of the studies are performed with RAPD markers in plants (Chalmers et al, 1992;Wolf andRijn, 1993, Bucci andMenozzi, 1995;Yeh et al, 1995;Maguire and Sedgley 1997;Gillies et al, 1997, Palácios andGonzález-Candelas, 1997;Gallois et al, 1998, Cattan-Toupance et al, 1998, Skabo et al, 1998, and in other organisms (Peever andMilgroom, 1994, Lou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and molecular markers have been used to enhance understanding of plant population genetic structure (Soltis et al, 1992). Among several efficient methods for revealing genetic variability within and among plant populations, some of the most widely applied are isozyme electrophoresis (Hamrick and Allard, 1972;Hamrick and Godt, 1990), random amplified DNA polymorphism -RAPDs - (Wolff and Peters-van Rijn, 1993;Wachira et al, 1995;Brummer et al, 1995;Swoboda and Bhalla, 1997;Palacios and Gonzalez-Candelas, 1997), and restriction fragment length polymorphisms -RFLPs - (Keim et al, 1989;Hong et al, 1993;Yanesita et al, 1997). In the genus Prosopis, previous isoenzymatic studies in some Algarobia Section species have shown low differentiation among species and populations coupled with high variability within populations (Saidman, 1985(Saidman, , 1986(Saidman, , 1990(Saidman, , 1993Saidman and Vilardi, 1987;Verga, 1995).…”
Section: Introductionmentioning
confidence: 99%